INNOVATION ORIENTATION TOWARD MARKET PERFORMANCE WITH INTEGRATED MARKETING COMMUNICATIONS AND ENTREPRENEURSHIP ORIENTATION AS MEDIATION VARIABLES (CASE STUDY ON SMALL MEDIUM BUSINESS IN PONTIANAK CITY) - Ema Trisnawati Nur Afifah Wenny Pebrianti (Equator Journal of Management and Entrepreneurship (EJME), 2021)
The purpose of this study was to test and analyze empirically the effect of innovation orientation on market performance in SMEs in Pontianak City using integrated marketing communication and entrepreneurial orientation mediation. The research methodology is based on a quantitative approach, using a questionnaire technique and the questionnaire items used are based on a literature review and several qualitative steps (interviews). The questionnaire was distributed to SME entrepreneurs in Pontianak City and a factor analysis was carried out to provide a descriptive picture of SMEs implementing innovation orientation, so that 93 respondents were obtained as the research sample. The results of the research after data processing using smartPLS 3.0 showed that there was an influence in innovation-oriented management on integrated marketing communication and entrepreneurial orientation, but it did not have a significant direct effect on the company's market performance. Likewise, the strategic activities of integrated marketing communications on market performance have no significant effect. Entrepreneurial orientation is able to significantly influence market performance, and as a mediator, this variable verifies that it is able to partially mediate the relationship between innovation orientation and firm market performance. However, the integrated marketing communication variable has no effect in mediating the relationship between innovation orientation and SME market performance in Pontianak City.Keywords: Small and Medium Enterprises, Innovation Orientation, Integrated Marketing ommunication, Entrepreneurship Orientation, Market Performance